Profiling of secondary metabolite and evaluation of anti-diabetic potency of Crotalaria quinquefolia (L): In-vitro, in-vivo, and in-silico approaches - Nazmun Nahar; Md. Nazmul Hasan Zilani; Partha Biswas; Md. Morsaline Billah; Shabana Bibi; Norah A. Albekairi; Abdulrahman Alshammari; Md. Nazmul Hasan (Saudi Pharmaceutical Journal, 2024)
Traditional medicinal plants have played a promising role in the human health system. In folklore medicine, Crotalaria quinquefolia L. is used to treat fever, pain, eczema, impetigo, lung infections, scabies. The present investigation was executed to identify secondary metabolites responsible for anti-diabetic potential of C. quinquefolia L. leaf extract along with their possible mechanistic pathways. The anti-hyperglycemic activity was assessed by in vitro α-amylase and α-glucosidase inhibitory assays and an in vivo oral glucose tolerance test and diabetogenic effect of streptozotocin in mice, followed by an integrative computational analysis. A total of 23 compounds were identified through GCMS and HPLC. The extract showed potent in-vitro α-amylase and α-glucosidase suppressive activity with IC50 values of 12.8 ± 0.1 µg/mL and 36.3 ± 0.07 µg/mL, respectively. In an in vivo oral glucose tolerance test, the extract (400 mg/kg body weight) prompted blood glucose levels to plummet by 18.9 % after 30 min, compared to the normal control and streptozotocin induced diabetes test, maximum glucose reduction was observed 11.67 % by dose of 200 mg/kg compared to the control; glibenclamide and extract (400 mg/kg) reduced blood glucose levels by 1.3 % and 16.7 %, respectively, compared to diabetic control at the end of the trial. Additionally, among the identified compounds, myricetin, quercetin, rutin, and kaempferol revealed good binding affinity as well as stability with the studied anti-diabetic proteins in docking and molecular dynamics simulation studies. Furthermore, QSAR analysis and network pharmacology studies of the identified compounds divulged enhanced insulin secretion stimulation, insulin receptor kinase activity, PPARγ expression; enzyme inhibition (α-glucosidase, α-amylase) and protection of the pancreas -mediated antidiabetic effects. Besides, they proved strong inhibitory potential against the studied antidiabetic proteins in other computational analysis. Based on the present findings, it can be affirmed that C. quinquefolia extract possesses anti-diabetic activity.